Dual antagonists of α5β1/αvβ1 integrin for airway hyperresponsiveness. Issue 22 (15th November 2020) - Sundaram, Aparna; Chen, Chun; Isik Reed, Nilgun; Liu, Sean; Ki Yeon, Seul; McIntosh, Joel; Tang, You-Zhi; Yang, Hyunjun; Adler, Marc; Beresis, Richard; Seiple, Ian B.; Sheppard, Dean; et al.
Graphical abstract: Abstract: Inhibition of integrin α5β1 emerges as a novel therapeutic option to block transmission of contractile forces during asthma attack. We designed and synthesized novel inhibitors of integrin α5β1 by backbone replacement of known αvβ1 integrin inhibitors. These integrin α5β1 inhibitors also retain the nanomolar potency against αvβ1 integrin, which shows promise for developing dual integrin α5β1/αvβ1 inhibitor. Introduction of hydrophobic adamantane group significantly boosted the potency as well as selectivity over integrin αvβ3. We also demonstrated one of the inhibitors (11 ) reduced airway hyperresponsiveness in ex vivo mouse tracheal ring assay. Results from this study will help guide further development of integrin α5β1 inhibitors as potential novel asthma therapeutics.